Molecular Characterization of Foot-and-Mouth Disease Virus Type O from Wild Pig in Bangladesh (Bangladesh Journal of Microbiology, 2016)
Foot-and-mouth disease (FMD) is a disease of all non-avian livestock animals which costs direct and indirect economic burden of 6.5-21 billion USD per year worldwide in endemic countries. In Bangladesh, FMD is endemic and mainly caused by foot-and-mouth disease virus (FMDV) serotypes O, A and Asia1. Among FMD susceptible animals cattle, sheep and goat were reported to be more susceptible to this virus, whereas, pig was reported as amplifier of the virus. To date there is no epidemiological data in Bangladesh defining the circulation of FMDV in pig population. This investigation first reports the circulation of FMDV in wild pigs of Bangladesh, its molecular characterization and genotyping. To pursue this, tissue sample from ruptured vesicles of mammary gland was collected from wild pig suspected to be infected with FMD followed by RT-PCR amplification, sequencing and phylogenetic study of the VP1 gene, which is the most variable region of FMDV genome. The virus was identified as FMDV serotype O and phylogenetically clustered together with India 2001 (Ind2001) lineage under middle-east, south Asia (ME-SA) topotype. Within the clade of Ind2001 lineage, FMDV from pig formed a sub-clade with 2013 sequences of cattle which indicates the phylogenetic relatedness of the virus from pig with circulatory virus in cattle population of Bangladesh in 2013. Pair-wise local alignment of the FMDV type O VP1 sequence of pig with other local cattle FMDV type O VP1 sequences of 2012 and 2013 supported the phylogenetic affiliation of the pig FMDV with the circulatory virus in cattle population of Bangladesh in 2013, whereas nucleotide sequences of cattle FMDV VP1 of 2012 were found to be 7-8% divergent compared to pig FMDV VP1. Phylogenetic and pair-wise alignment data conclusively revealed that (i) homologous circulation of the FMDV type O (Ind2001 lineage) occurs in both animal traits; and (ii) FMDV type O VP1 sequence of pig origin is distantly related to 2012 local FMDV type O VP1 sequences of cattle origin, but closely related to 2013 local cattle FMDV type O VP1.Bangladesh J Microbiol, Volume 31, Number 1-2,June-Dec 2014, pp 41-45